(untitled) (Balthazar, 2022)
The artistic output of Etel Adnan, both in writing and in painting, is a sanctuary of the memory of diverging countries, languages, cultures and societies. The lives Adnan lived, as woman and committed artist and feminist, revolve around the experience of different places and idioms, creating an art bound to a hand-to-hand with life.